Correlation of angiographic and surgical findings in distal coronary branches. - Pidgeon, J (1984)
In 60 consecutive patients undergoing vein graft surgery the angiographic appearances of the coronary vessels were compared with those of the vessels at operation. On the basis of lumen diameter at the potential sites for grafting it was possible to predict with reasonable accuracy from examination of the angiogram which vessels were large enough to be grafted. Angiographic predictive accuracy was 82% and was similar both for vessels which filled normally and for those which filled by collaterals. The predictive value of the angiographic assessment was similar for branches thought to be too small (predictive value 74%) and for those considered sufficiently large (predictive value 85%) to receive a vein graft. Disease of the vessel walls was found at surgery (66% of coronary branches examined) more frequently than was predicted from the angiographic appearances (33%). Previous necropsy studies have found a high prevalence of coronary atheroma in the population, yet normal angiographic appearances in the coronary arteries are not uncommon in patients undergoing investigation for suspected coronary disease. The present study showed that atheroma may be present in coronary vessels without encroaching into the vessel lumen, so that it is not evident on the angiogram. Coronary atheroma is thus present more often and is more widely distributed in the coronary tree than is indicated by coronary angiography.